Nitrogen doped lotus stem carbon as electrocatalyst comparable to Pt/C for oxygen reduction reaction in alkaline media. (10th August 2017) - Weththasinha, H.A.B.M.D.; Yan, Zaoxue; Gao, Lina; Li, Yuan; Pan, Denghui; Zhang, Mingmei; Lv, Xiaomeng; Wei, Wei; Xie, Jimin
Abstract: The nitrogen doped carbon with high content of pyridine N and porous structure indicates high activity for oxygen reduction reaction (ORR). In this paper, nitrogen doped lotus stem carbon (N-LSC) with 6.3 at% of N (containing 52 at% of pyridine N) and porous structure is developed by using lotus stem as carbon source and dopamine hydrochloride as nitrogen source. The ORR activity, stability and methanol tolerance are characterized. The results show that the N-LSC has comparable activity to Pt/C, and much better methanol tolerance and stability than Pt/C. The porous structure and high content of pyridine N are believed to lead to the high ORR performances of the N-LSC. Highlights: Mesoporous N doped lotus stem carbon (N-LSC) is synthesized. The N-LSC has 6.3 at% of N containing 52 at% of pyridine N. The N-LSC shows comparable ORR activity to Pt/C.